"Without the spelling errors I would have shortlisted her…": The impact of spelling errors on recruiters' choice during the personnel selection process. (September 2017) - Martin‐Lacroux, Christelle
Abstract : Despite the time spent on writing at work and employers' dissatisfaction with their employees' spelling skills, little is known about recruiters' attribution, and decision making when they read application forms with spelling errors. This study examines the impact of spelling and typographic errors on recruiters' attributions about applicants, and on their shortlisting decision. Based on a sample of 20 French recruiters, we conducted an experiment to collect both qualitative data through the verbal protocol method and quantitative data. Specific verbal reports are associated with different types of errors. Recruiters also form attributions about candidates. We demonstrate that spelling errors affect recruiters' behavior more negatively than typographic ones. We discuss the implications of these findings for researchers and practitioners.